2014
DOI: 10.1267/ahc.14037
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Hsp27 in the Rat Submandibular Gland Following the Application of Various Surgical Treatments

Abstract: Salivary glands repair and regenerate following various types of injuries and surgical procedures. However, the tissue responses induced in the contralateral glands have yet to be elucidated in detail. Hsp27, a member of the heat-shock protein (Hsp) family, is strongly expressed in physiological environments, particularly during development. Hsp27 was previously shown to play a role in the regulation of acinar cell proliferation and differentiation in the rat submandibular gland.The present study performed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The quantitative compensation of secretory function by proliferation of acinar cells and MECs during regeneration has also been reported [15, 40, 41]. Our recent study showed that salivary gland resection induced acinar cell differentiation from the intercalated duct in the residual tissue of the operated side, as well as the NC side in adult rats [25]. An increased salivary secretion from the residual acini is necessary to complement decreased glandular tissue resulting from surgery resection.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The quantitative compensation of secretory function by proliferation of acinar cells and MECs during regeneration has also been reported [15, 40, 41]. Our recent study showed that salivary gland resection induced acinar cell differentiation from the intercalated duct in the residual tissue of the operated side, as well as the NC side in adult rats [25]. An increased salivary secretion from the residual acini is necessary to complement decreased glandular tissue resulting from surgery resection.…”
Section: Introductionmentioning
confidence: 74%
“…Surgery on the submandibular gland was performed using the procedure reported by Mizobe et al [25]. Under general anesthesia with an intraperitoneal injection of 1 mL/kg pentobarbital sodium (Somnopentyl, Kyoritsu Seiyaku, Tokyo, Japan), the rat was placed in a supine position, an incision was made in the right submandibular skin, and connective tissue was dissected while avoiding damage to the surrounding tissue, including nerves and blood vessels .…”
Section: Methodsmentioning
confidence: 99%